(untitled) (Agroindustria, Sociedad y Ambiente, 2013)
The purpose of this research was the evaluation of a sensory panel for the development of descriptive profile of a commercial protein concentrate through quantitative analysis descriptive technique (AQD). To do this it was necessary to recruit, select and train a discriminative sensory panel composed of technical staff working in CIEPE Foundation. Among the pre-selection criteria, of the 25 participants, included: the availability of time, health condition and eating habits. Shortlisted candidates were trained for a period of 12 weeks, following guidelines of ISO 8586-1 and ASTM SP758. The sensory description was a commercial protein concentrate. For this, Two evaluations were performed, were determined in the first descriptors associated with different product attributes and the second was quantified each identified descriptors. To record the intensity of each attribute was applied a form composed of unstructured scale. To verify the consistency of the judgments by the panelists, we used analysis of variance (ANOVA) for the descriptive profile of the main attributes of the product. The applied methodology allowed the formation of a trained sensory panel, consisting of 7 individuals (3 men and 4 women), according to the guidelines established in the rules and criteria Jellinek (1985). Descriptive profile was obtained from the analyzed protein concentrate, which is comprised of eight descriptors: ferrous, ivory, astringency, cooked milk, dairy odor, sweet, fatty commercial milk.